Management Model Based on Lean Warehousing & Lean Logistic to Increase the Level of Service in SMEs in a Hardware Store - Taquía Gutiérrez, José Antonio (2023)
In recent years, the trading industry in Peru has experienced a remarkable growth. However, they face several problems such as varying demand, delays in order delivery and having to offer high quality products quickly at low cost. Small and medium-sized enterprises (SMEs) account for 95% of companies, so it is necessary to implement productivity tools. In the study, the proposed model is to improve the level of service, first we will collect data through value stream map, Pareto diagram and problem tree, then we will implement the proposed methodologies and at the end we will reevaluate the indicators. Inventory processes were also simulated to reduce waste and costs.